STUDI PENGGUNAAN ANTIHIPERTENSI PADA PASIEN PREEKLAMPSIA DI RUMAH SAKIT “X” - Goreti, Meilinda; Victoria Yulita Fitriani (Jurnal Informatika Medis, 2025)
Preeclampsia is a complication of pregnancy occurring after 20 weeks of gestation, characterized by elevated blood pressure accompanied by proteinuria. The aim of this study was to identify the patient characteristics, antihypertension usage profile, and the occurrence of Drug Related Problems (DRPs) in preeclampsia patients admitted to Hospital “X” during the period of January to December 2023. This observational study was conducted retrospectively using purposive sampling for data collection. The results obtained from 75 patients showed that the majority were aged 26–35 years (49.3%), with parity P0 (42.67%), primigravida pregnancy status (G1) (40%), last education level at senior high school (46.67%), no history of hypertension (74.67%), no history of preeclampsia (94.67%), and obese BMI (49.33%). The preeclampsia patients based on risk factors were dominated by those with parity P0 (first delivery), totaling 32 patients (36.55%). Blood pressure readings above 160 mmHg were found in 76% of patients, and proteinuria at 2+ was observed in 41.3%. The most commonly used antihypertension medication was single-agent nifedipine (81.33%), while the most frequently used non- antihypertension drug was 40% magnesium sulfate (MgSO4) (82.66%). The incidence of DRPs included 14 cases (18.33%) of drugs without indication, 13 cases (17.32%) of indication without drug therapy, and moderate drug interactions between dexamethasone and furosemide in 20 patients (26.66%). The potential adverse drug reactions observed were minor (20%), moderate (80%), and none were major (0%). This study is expected to serve as an informative reference regarding the use of antihypertension therapy in preeclampsia patients. Kata kunci: Preeclampsia, Antihypertension, Retrospectiv, Problem, Drug